El método de descubrimiento para el aprendizaje de biología en los estudiantes de segundo año de bachillerato de la Unidad Educativa Salesiana Domingo Savio de Cayambe. - Quimbiulco Borja, Ritha Lourdes (2013)
From the perspective of the “Domingo Savio” Salesian Educational Unit from Cayambe, the discovery learning constitute a practice that needs more often and guide to achieve better results in the subject of Biology. Although in this paper we show some factors such as participatory research, problem solving and activities with which knowledge is constructed, it is building a practice contact recreation and nature is an important element in the learning construct. The different challenges presented in the educational unit in the planning aspect of the class, as the number of students, few materials and lack of interest of students and parents, contribute to the not expected results.